Electronic library for the Universiti of Teknologi Petronas - Fikelepi, Zintle (Universiti Teknologi Petronas, 2005)
Both corporate and academic institutions are required to be flexible and adaptable to the ever changing technological environment. Electronic or digital libraries are just one of the instruments through which academic institutions can adapt to the changing environment as well as meeting the demands of the student. The overall objective of the study is to identify important variables namely; knowledge management, information accessibility and digital libraries for consideration at the implementation phase, and thus enable successful implementation of a valid electronic library. The project methodology will follow a hybrid methodology composed of both the SDLC and Summit D methodologies. Analysis, requirements gathering, and other activities are some of the few tasks, enabling researchand ultimately a working prototype. The final output of the paper will be a full scale implementation of an e-library for the Universiti Teknologi Petronas. Such an implementation will see the institution breaking new ground in information technologies and knowledge management. By its nature academic institutions impart knowledge, thus an implementation of an electronic library will seek to facilitate UTP in ensuring that knowledge, information are imparted to all stakeholders, in particular the students. Information, knowledge, will be made available and thus ensure proper utilization of these resources.